Pembaharuan Hukum Nasional Dalam Upaya Perlindungan Data Pribadi Di Era Distrupsi Kecerdasan Buatan (Artificial Intelligence) - Abdul Hadi; Bima Guntara (Jurnal Hukum Mimbar Justitia, 2022)
Entering the era of disruption of artificial intelligence (AI) does not rule out the possibility of increasing lysophisticated criminal acts carried out using virtual media. Cyber crime refers to a crime related to cyber space and crimes that use computers. Cyber criminals or data hacker salso take advantage of AI technology to steal personal data. There fore, information regarding personal data is very important tobe protected, so that data leak age does not occur, because it contains a lot of information related to a person. This study used normative legal research method with statutory and conceptual approach. This study reveals that Indonesia currently don’t have a legal umbrella that particularly regulates personal data protection, however, the regulation on personal data protection has been spread in various law sand regulation salthoughit does not clearly or specifically mention personal data protection.Keywords : Legal Reform, Personal Data, Artificial Intelligence.